2009
DOI: 10.3400/avd.oa08029
|View full text |Cite
|
Sign up to set email alerts
|

Skin Perfusion Pressure is a Useful Tool for Evaluating Outcome of Ischemic Foot Ulcers with Conservative Therapy

Abstract: Objectives: This study intended to confirm whether skin perfusion pressure (SPP) could predict the outcome of ischemic wound healing. Patients and methods: Sixty-two limbs in 53 patients with conservative therapy were enrolled in this study. A SPP value of 40 mmHg was adopted as the criterion for making clinical decisions. The outcome one month after SPP measurement was classified as "improved" (diameter of ulcer decreased ≥ 20% or demarcation of gangrene became well defined) or "no change or worse" (others), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Endovascular treatment was the first choice for TASC A and B lesions in the iliac region, and bypass surgery for TASC C and D lesions. 5 In most patients with infra-inguinal arterial lesions, bypass surgery was performed, and endovascular treatment was adopted only for short-segment lesions in the superficial femoral artery. Generally, we aimed at complete revascularization to the pedal arch, often with aggressive bypass surgery to crural or foot arteries.…”
Section: Treatment Strategy and Postoperative Surveillancementioning
confidence: 99%
“…Endovascular treatment was the first choice for TASC A and B lesions in the iliac region, and bypass surgery for TASC C and D lesions. 5 In most patients with infra-inguinal arterial lesions, bypass surgery was performed, and endovascular treatment was adopted only for short-segment lesions in the superficial femoral artery. Generally, we aimed at complete revascularization to the pedal arch, often with aggressive bypass surgery to crural or foot arteries.…”
Section: Treatment Strategy and Postoperative Surveillancementioning
confidence: 99%
“…The postoperative SPP values in group N were better than those in group U but less than those in group H. Compared with group H, group N featured more patients with chronic kidney disease and group U had even more. Additionally, groups N and U included more patients with diabetes than group H; therefore, the patients in groups N and U could have had more advanced distal lesions than did the patients in group H. [12][13][14] Previous studies have suggested a value of 30 mmHg 1,2,6) or 40 mmHg 4,5) to be the critical SPP threshold necessary for wound healing. In the present study, 50% of the limbs had a mean postoperative SPP value of <30 mmHg in group U, consistent with the results of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[4][5][6] We started SPP measurements following the establishment of a vascular laboratory at our institution in August 2008. Although the number of examinations of SPP is still small in our institution at present, we deemed it useful to have an initial evaluation of its effectiveness by retrospectively assessing the changes in SPP values obtained between the pre-and postoperative periods 8,9) and the relationship between the SPP values and ulcer healing, in order to assess the utility of SPP measurement in evaluating the outcome of arterial reconstructions in patients with CLI caused by arteriosclerosis obliterans (ASO).…”
Section: Skin Perfusion Pressure Measurement To Assess Improvement Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin perfusion pressure (SPP) is one of the useful tools for evaluating outcome of ischemic foot ulcer with conservative therapy, as Urabe et al reported. 10) It seemed that SPP may be one of the assisted predictors of quality of the perfusion of the sural artery bypass before the ulcer recurrence. Barral et al reported that bypass to a perigeniculate vessel alone may not be sufficient to allow tissue healing in the patient with extensive foot necrosis, 2) and such patients may require a more distal bypass to achieve limb salvage.…”
Section: Discussionmentioning
confidence: 99%